O46 Differences in ARCP outcome by surgical specialty: a longitudinal cohort study. (30th July 2021) - Hope, C; Lund, J; Griffiths, G; Humes, D
Abstract: Introduction: Surgical training in the UK is comprised of ten specialties: cardiothoracic, general, neurosurgery, oral and maxillofacial (OMFS), otolaryngology, paediatric, plastic, trauma and orthopaedics, urology and vascular surgery. Progression through training is assessed by the Annual Review of Competency Progression (ARCP). The aim is to examine ARCP outcomes within UK surgical specialty training and identify differences between specialties. Method: A longitudinal cohort study using data from United Kingdom Medical Education Database (UKMED) was performed across surgical specialities. ARCP outcome was the primary outcome measure. Multi-level univariate and multiple ordinal regression analyses were performed. Result: 8, 220 trainees with an ARCP outcome between 2010 and 2017 were included, comprising 31, 788 ARCP outcomes. There was substantial variation in the proportion of non-standard outcomes across specialties with general surgery trainees having the highest proportion of non-standard outcomes (22.5%) and urology trainees the fewest 12.4%. After adjustment, general surgery trainees were 1.3 times more likely to receive a non-standard outcome compared to T&O trainees (OR 1.33 95% CI 1.21–1.45). Urology trainees were 36% less likely to receive a non-standard outcome compared to T&O trainees (OR 0.64 95% CI 0.54–0.75). Female trainees and older age were associated with non-standard outcomes (OR 1.11 95% CI 1.02–1.22; OR 1.04 95% CI 1.03–1.05). Conclusion: There is wide variation in the outcomes of surgical ARCP's across specialties. General surgery has higher rates of non-standard ARCP outcomes compared to other surgical specialities. Across all specialities, female sex and older age were associated with non-standard outcomes. Further studies are required to explore these associations. Take-home Message: There is significant variation in ARCP outcomes between specialities. Women and older trainees receive significantly more non-standard outcomes.